Primitive Neuro Ectodermal Tumor (PNET) in infant diagnosed by histopathology and immunohistochemistry techniques (Medical Journal of Indonesia, 2007)
Primitive Neuro Ectodermal Tumor (PNET) is rare and difficult to diagnose. A case of PNET was diagnosed based on histopathological and immunohistochemical findings. A 4-month-old infant was admitted to the hospital with a tumor on the midline of his chest wall since he was 3 days old. The tumor was fixed on the chest wall and had ill-defined margin, enlarged over time and reached more than 10 cm in diameter when he was brought to a clinician. Two small ulcers were seen on the skin overlying the tumor. It was diagnosed as soft tissue tumor suggestive of a hemangioma. The tumor was 17 x 13 x 5.5 cm in size, white colored and firm to the touch. Microscopic examination revealed malignant small round cells with round to ovoid nuclei, coarse chromatin and scanty cytoplasm. Most cells were arranged in a solid pattern with scattered Homer-Wright rosettes. The mitotic count was 7/10 HPF, and necrosis was minimal (less than 25%). On immunohistochemical examination, the cells showed weak to moderate immunoreactivity to Vimentin and CD99, but showed negative to weak positive reactivity to NSE and Chromogranin. Based on the clinical features, gross findings, histopathologic and immunohistochemical examinations, the case was diagnosed as a malignant small round cell tumor consistent with PNET / ES (Ewing's Sarcoma). To confirm the diagnosis, cytogenetic examination is suggested. (Med J Indones 2007; 16:108-12) Keywords: PNET, histopathology, immunohistochemistry